A Rare Case of Dual Primary Supratentorial Glioma and Infratentorial Meningioma - Yip, Chi-Man; Jan, Chia Ing (Journal of Neurological Surgery Reports, 2024)
Introduction Gliomas and meningiomas are two common primary brain tumors, but occurring simultaneously in the same patient is a rare entity. The authors would like to report a case of coexistence of a superior parietal lobule diffuse glioma, IDH-wild type, histologically CNS WHO grade 3 and a left posterior fossa transitional meningioma, WHO grade 1; both the tumors were successfully removed in one-stage operation.Case Presentation A 68-year-old female having hypertension, who presented to us with the chief complaints of involuntary shaking of her left lower limb associated with her left upper limb tingle, dizziness, and neck soreness. She was found to have a lesion in her right parietal region and a tumor in her left cerebellar region. After detailed discussion with the patient and thorough preoperative evaluation, the authors performed a right parietal craniotomy and a left retrosigmoid approach in one-stage operation to remove both the tumors, which were proven to be of two distinct histological identities.Conclusion The management for two tumors located far apart needs a case-by-case evaluation. An important aspect while dealing with such cases is to decide which tumor needs to be operated first or whether both lesions can be operated at the same time with one-stage operation.
Keywords: dural primary brain tumors; one-stage operation; infratentorial meningioma; supratentorial glioma